Production Engineering and Management
It is our pleasure to introduce the seventh edition of the International Conference on Production Engineering and Management (PEM), an event that is the result of the joint effort of the University of Trieste and the Ostwestfalen- Lippe University of Applied Sciences. The conference has been established as an annual meeting under the Double Degree Master Program “Production Engineering and Management” by the two partner universities. This year the conference is hosted at the university campus in Pordenone. The main goal of the conference is to offer students, researchers and professionals in Germany, Italy and abroad, an opportunity to meet and exchange information, discuss experience, specific practices and technical solutions for planning, design and management of manufacturing and service systems and processes. As always, the conference is a platform aimed at presenting research projects, introducing young academics to the tradition of symposiums and promoting the exchange of ideas between the industry and the academy. This year’s special focus is on industry sustainability, which is currently a major topic of discussion among experts and professionals. Sustainability can be considered as a requirement for any modern production processes and systems, and also has to be embedded in the context of Industry 4.0. In fact, the features and problems of industry 4.0 have been widely discussed in the last editions of the PEM conference, in which efficiency and waste reduction emerged as key factors. The study and development of the connections between future industry and sustainability is therefore critical, as highlighted in the recent “German Sustainable Development Strategy and the 2030 Agenda”. Accordingly, the seventh edition of the PEM conference aims to offer a contribution to the debate. The conference program includes 25 speeches organized in six sessions. Three are specifically dedicated to “Direct Digital Manufacturing in the context of Industry 4.0” and “Technology and Business for Circular Economy and Sustainable Production”. The other sessions are covering areas of great interest and importance to the participants of the conference, which are related to the main focus: “Innovative Management Techniques and Methodologies”, “Industrial Engineering and Lean Management” and “Wood Processing Technologies and Furniture Production”. The proceedings of the conference include the articles submitted and accepted after a careful double-blind refereeing process.